Past quit attempts in a national sample of Aboriginal and Torres Strait Islander smokers. (1st June 2015) - Nicholson, Anna K; Borland, Ron; Davey, Maureen E; Stevens, Matthew; Thomas, David P
Abstract: Objectives : To describe past attempts to quit smoking in a national sample of Aboriginal and Torres Strait Islander people, and to compare their quitting activity with that in the general Australian population. Design, setting and participants: The Talking About The Smokes (TATS) project used a quota sampling design to recruit participants from communities served by 34 Aboriginal community‐controlled health services and one community in the Torres Strait. We surveyed 1643 smokers and 78 recent quitters between April 2012 and October 2013. Baseline results for daily smokers ( n = 1392) are compared with results for daily smokers ( n = 1655) from Waves 5 to 8.5 (2006–2012) of the Australian International Tobacco Control Policy Evaluation Project (ITC Project). Main outcome measures: Ever having tried to quit, tried to quit in the past year, sustained a quit attempt for 1 month or more. Results: Compared with the general population, a smaller proportion of Aboriginal and Torres Strait Islander daily smokers had ever tried to quit (TATS, 69% v ITC, 81.4%), but attempts to quit within the past year were similar (TATS, 48% v ITC, 45.7%). More Aboriginal and Torres Strait Islander daily smokers than those in the general population reported sustaining past quit attempts for short periods only. Aboriginal and Torres Strait Islander smokers whose local health services had tobacco control resources were more likely to have tried to quit, whereas men and people who perceived they had experienced racism in the past year were less likely. Younger smokers, those who had gone without essentials due to money spent on smoking, and those who were often unable to afford cigarettes were more likely to have tried to quit in the past year, but less likely to have ever sustained an attempt for 1 month or more. Smokers who were unemployed, those who had not completed Year 12 and those from remote areas were also less likely to sustain a quit attempt. Conclusion s : Existing comprehensive tobacco control programs appear to be motivating Aboriginal and Torres Strait Islander smokers to quit but do not appear to overcome challenges in sustaining quit attempts, especially for more disadvantaged smokers and those from remote areas.